Use Of Digital Platforms In Improving Competetive Advantages In 37 State Primary Schools In Pekanbaru City - Yanti, Aprida Yanti; Safitri, Dea Duwi; Islami, Fitri (Khalifah : Jurnal Pendidikan Nusantara, 2024)
Increasing the competitiveness of educational institutions is a big challenge in the digital era, including at SDN 37 Pekanbaru. This research aims to analyze the use of digital platforms, especially Merdeka Belajar, in increasing school competitive advantages. A qualitative descriptive approach was used with interview, observation and documentation methods. The research results show that although digital platforms provide significant benefits, such as improving the quality of learning and evaluation, technological infrastructure challenges, user resistance, and budget constraints still hinder optimal implementation. Limited digital marketing strategies are also an obstacle in increasing school visibility. The research conclusion states that the use of digital platforms needs to be supported by intensive training, infrastructure improvements, and active collaboration between teachers, students and parents to achieve sustainable competitiveness.